The female image in the system of spiritual values of drama by M. Kostomarov (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article highlights women’s characters in the М. Kostomarov’s tragedies «Sava Chaly» and «Pereyaslavska night» in terms of system of moral values. The point of specific literary analysis has been the character of Katerine and Marine as the embodiment of an ideal woman. The yact as carriers incamates moral, ethic, esthetic, humane, civic, social, national and syncretic Pra values.
Keywords: character; ideal; the system of moral values; morality; mentality